Multifunctional nanoparticles: from the detection of biomolecules to the therapy. (22nd February 2010) - Roux, Stephane; Tillement, Olivier; Billotey, Claire; Coll, Jean-Luc; Duc, Geraldine; Marquette, Christophe; Perriat, Pascal
The intense research activities devoted to nanotechnology led to the development of a wide variety of multifunctional nanoparticles. Besides their small size which opens the route to the exploration of living matter at the subcellular scale, the properties of these particles can be accurately tuned by varying the composition, the size, the shape and the chemical composition of the surface. Some of these particles are peculiarly suited for biological and biomedical applications. This review provides an overview on the sensing and biomedical applications of multifunctional gold and gadolinium oxide nanoparticles which were developed by a network of some laboratories of Rhone-Alpes Region.